2011 IEEE International Electric Machines &Amp; Drives Conference (IEMDC) 2011
DOI: 10.1109/iemdc.2011.5994770
|View full text |Cite
|
Sign up to set email alerts
|

Optimised Segmental Rotor Switched Reluctance Machines with a greater number of rotor segments than stator slots

Abstract: Segmental Rotor Switched Reluctance Machines have been demonstrated to produce significantly more torque than Conventional Switched Reluctance Machines because each coil is able to link more magnetic flux. In previous work the range of topologies studied has been relatively restricted; there has been no consideration of the range of stator tooth and rotor segment number options and the designs have not been formally optimised in any way. This paper seeks to address this: using Finite Element toolsets for optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Increasing the number of rotor poles of SRM and SSRM was proposed in [5], [7], and [18]. It was reported that use of a higher number of rotor poles increases the torque output and reduces copper loss.…”
Section: A Effect On Torque Outputmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing the number of rotor poles of SRM and SSRM was proposed in [5], [7], and [18]. It was reported that use of a higher number of rotor poles increases the torque output and reduces copper loss.…”
Section: A Effect On Torque Outputmentioning
confidence: 99%
“…It was reported that such machines give about 40% higher torque Manuscript than conventional SRM for the same frame size and copper loss. A topology of segmented rotor SRM (SSRM) with higher number of rotor segments than stator poles was proposed in [7]. Such machines are reported to have about 65% higher torque for the same frame size and copper loss than conventional SRMs [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in reduction of average torque of the motor. In order to address these issues, SSRM with higher number of rotor segments than stator slots is introduced [5]. This configuration increases the available slot area which results in increased torque output.…”
Section: Introductionmentioning
confidence: 99%